KULTUREL DYNAMIK I OPLEVELSESBYRUMMET – EN ANALYSE AF BRANDTS KLÆDEFABRIK - Brandrup, Hjørdis Havsteen (K&K - Kultur og Klasse, 2010)
CULTURAL DYNAMIC IN THE URBAN EXPERIENCE SCAPE – AN ANALYSIS OF BRANDTS KLÆDEFABRIK Brandts Klædefabrik (Brandt’s Textile Mill) is a cultural cluster in the city of Odense, Denmark. The cultural experiences available at Brandts Klædefabrik cover a wide field and are relevant for people of all levels of education and all ages, embracing as they do not only fine culture but also triviality and excitement. Brandts Klædefabrik is therefore a culturally inclusive place, although its symbolic power is dominated by a cultural and economic elite trying to maintain an exclusively controlled social and physical order in the urban space. However, Brandts Klædefabrik is part of a city which contains a wide range of cultural groups: a Danish cultural elite, immigrants, homeless people and drug addicts. In this cultural multiplicity Brandts Klædefabrik is a cultural cluster and an urban entertainment district which does not include marginalised groups. Paradoxically, the attempt to maintain an exclusive order to satisfy an audience with buying power runs against the creative profile of the area, in which cultural and social multiplicity are important values. The area around Brandts Klædefabrik is a public space; but if it is going to be a public domain and the scene of cultural exchanges between different groups in the city, it needs to become more culturally inclusive. Brandts Klædefabrik may turn into a public domain if a cultural dynamic and multiplicity are given the chance to unfold there.